PENERAPAN KEADILAN RESTORATIF SEBAGAI ALTERNATIF PENYELESAIAN PADA TINDAK PIDANA PENCURIAN - Rachmat Andika Prasetyo; Mohamad Ismed; Achmad Fitrian (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The restorative justice approach has increasingly developed as an alternative mechanism for resolving criminal cases by emphasizing the restoration of relationships between offenders, victims, and the community. Nevertheless, the implementation of restorative justice must continue to ensure the protection of offenders’ legal rights, particularly the right to legal counsel. The primary issue addressed in this study concerns how to guarantee that restorative processes, which are inherently dialogical and consensual, remain fair, voluntary, and consistent with the principle of legal protection for offenders as subjects of law with rights and obligations. This research employs a normative legal research method, utilizing statutory and conceptual approaches. The legal materials consist of primary legal sources in the form of laws and policies related to restorative justice, as well as secondary legal sources including books, academic journals, and legal doctrines. Legal materials were collected through library research and analyzed qualitatively using deductive reasoning to examine the role and position of legal counsel within the restorative justice process. The findings of this research indicate that the regulation of restorative justice in the settlement of theft offenses in Indonesia is not contained within a single, unified legal instrument, but is instead dispersed across various complementary statutory and regulatory frameworks, including the objectives of sentencing as stipulated in Article 51 of Law Number 1 of 2023 on the Criminal Code, the provisions of the Criminal Procedure Code, the Law on the Indonesian National Police, Regulation of the Indonesian National Police Number 8 of 2021, and Supreme Court Circular Letter Number 4 of 2014, which collectively and normatively emphasize an orientation toward restoration, conflict resolution, and substantive justice. In practice, restorative justice has been implemented by law enforcement authorities, particularly at the investigation stage through penal mediation mechanisms, involving dialogue between offenders and victims to achieve amicable settlements, restitution of losses, and the affirmation of offender responsibility, especially in cases of minor theft; however, its application remains subject to specific criteria, thereby positioning restorative justice as a complementary mechanism rather than a substitute for the formal criminal justice system